2022
DOI: 10.1002/ppul.26098
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Ureaplasma is associated with small airway obstruction in extremely preterm infants

Abstract: Background: The long-term follow-up of lung function (LF) in extremely preterm (EP) infants with bronchopulmonary dysplasia (BPD) has shown a worldwide increase in small airway obstructions (SAO).Objectives: We investigated the relationships between intrauterine Ureplasma infection in EP infants and bubbly/cystic lung, BPD, and SAO at school age. Methods: Placental pathology, placental Ureaplasma DNA (pU-DNA), and cord blood immunoglobulin M (IgM) (C-IgM) were investigated in 360 EP infants born from 1981 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…These findings are similar to those of the interstitial BPD phenotype, which is characterized by an increase in fibrotic tissue and a widening of the interstitial spaces [8,96]. Although it is difficult to derive specific information from chest radiographs, it is noteworthy that Ureaplasma infection/colonization in extremely preterm infants has been associated with cystic-emphysematous changes [97,98]. This may be suggestive of a parenchymal BPD phenotype [8].…”
Section: Linking Ureaplasma Endotype With Bpd Phenotypessupporting
confidence: 70%
See 1 more Smart Citation
“…These findings are similar to those of the interstitial BPD phenotype, which is characterized by an increase in fibrotic tissue and a widening of the interstitial spaces [8,96]. Although it is difficult to derive specific information from chest radiographs, it is noteworthy that Ureaplasma infection/colonization in extremely preterm infants has been associated with cystic-emphysematous changes [97,98]. This may be suggestive of a parenchymal BPD phenotype [8].…”
Section: Linking Ureaplasma Endotype With Bpd Phenotypessupporting
confidence: 70%
“…This may be suggestive of a parenchymal BPD phenotype [8]. Finally, Kitajima et al reported that intrauterine Ureaplasma infection in extremely preterm infants was associated with signs of moderate to severe small airway obstruction in lung function tests at school age [97]. These findings are compatible with the peripheral airway BPD phenotype [8].…”
Section: Linking Ureaplasma Endotype With Bpd Phenotypesmentioning
confidence: 91%
“…In our previous report, intrauterine Ureaplasma infection in EP infants was associated with longterm respiratory impairment. 32 Lung destruction may have started earlier in these infants. In the future, we need to further investigate the earlier measurement of desmosine/ creatinine levels to clarify the utility of urine desmosine as a better biomarker for early BPD detection.…”
Section: Discussionmentioning
confidence: 94%